Net loss statistics underestimate carbon emissions from mangrove land use and land cover change. Issue 4 (21st November 2021) - Bukoski, Jacob J.; Dronova, Iryna; Potts, Matthew D.
Abstract : Converting mangroves to other land cover types can induce large emissions of carbon dioxide, depending on the type of land use and land cover (LULC) change. However, mangroves may also recover their ecosystem carbon stocks rapidly following restoration, potentially offsetting carbon stock losses. While studies have quantified these tradeoffs at global scales using coarse metrics, fewer studies have quantified them at national scales at higher resolution. Here, we used high‐resolution data sets of LULC for mangroves in Thailand to quantify district‐level gross and net changes in mangrove carbon stocks from 1960 to 2014. We found emissions based on gross gain and loss statistics (7.18 ± 0.24 million Mg C) to be greater than those associated with emissions based on net area change statistics (1.65 ± 0.26 million Mg C) by a factor of four. The difference in estimates arises from slower rates of carbon stock recovery following reforestation relative to carbon stock loss following LULC change. Overall, we found the greatest gains in mangrove carbon stocks to be from mangrove expansion in areas of accreting sediments, which were strongly correlated with district‐level extent of undisturbed mangroves. Our results show that net loss statistics may greatly underestimate emissions associated with LULC change in mangroves. Additionally, our findings suggest that gains in mangrove carbon stocks associated with natural establishment at the periphery of standing mangroves may offset substantial carbon stock losses at national scales.